2014
DOI: 10.1007/s10067-014-2752-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of physicians’ illness perception of fibromyalgia with frustration and resistance to accepting patients: a cross-sectional study

Abstract: The aim of this study was to elucidate whether physicians' illness perceptions correlate with their frustration or resistance to accepting patients with fibromyalgia (FM). In this cross-sectional postal survey, questionnaires were sent to member physicians of the Japan College of Rheumatology and Japan Rheumatism Foundation. Measures collected included the Brief Illness Perception Questionnaire with Causal Attribution, the Illness Invalidation Inventory, and the Difficult Doctor-Patient Relationship Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 34 publications
2
26
0
2
Order By: Relevance
“…Among these individuals, only 12.5% were actually diagnosed by a physician 34. In addition, among Japanese physicians who had previously treated fibromyalgia patients, less than half (44.2%) self-reported wanting to accept more patients with this chronic pain condition 35. Furthermore, cross-national data showed that Japan had the lowest rate of pain reported (4.4%) and treated (26.3%), compared to other developed countries, including the USA (23.8% experienced pain and 40.1% treated) and Europe (including the UK, France, Germany, Italy, and Spain; 20.2% experienced pain and 47.0% treated) 36.…”
Section: Discussionmentioning
confidence: 99%
“…Among these individuals, only 12.5% were actually diagnosed by a physician 34. In addition, among Japanese physicians who had previously treated fibromyalgia patients, less than half (44.2%) self-reported wanting to accept more patients with this chronic pain condition 35. Furthermore, cross-national data showed that Japan had the lowest rate of pain reported (4.4%) and treated (26.3%), compared to other developed countries, including the USA (23.8% experienced pain and 40.1% treated) and Europe (including the UK, France, Germany, Italy, and Spain; 20.2% experienced pain and 47.0% treated) 36.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians might also be frustrated as a result of difficulties in controlling the symptoms and the patients' emotional responses to the syndromes [6]. Furthermore, it is often assumed that functional limitations in FSS patients are less severe than those in patients with well-defined medical diseases (MD).…”
Section: Introductionmentioning
confidence: 99%
“…De esta forma, los pacientes no sólo tienen que soportar el dolor y el resto de síntomas incapacitantes característicos de la enfermedad, sino que también tienen que lidiar con la incredulidad existente por parte de los profesionales que cuestionan su existencia y la asocian con componentes psicológicos (Briones Vozmediano, 2018;Colmenares Roa et al, 2016;Crooks, 2015;Gill Taylor et al, 2016;Reibel & Pearson, 2017). Estas percepciones influyen en la relación y afectan a la calidad de la atención, al retraso del diagnóstico y a la toma de decisiones acerca del tratamiento (Briones Vozmediano et al, 2018;Homma et al, 2016), de manera que los pacientes se sienten insatisfechos, incomprendidos e injustamente tratados con la atención recibida y se encuentran en un estado de ansiedad y frustración continua (Briones Vozmediano et al, 2018;Durif Bruckert et al, 2015;Roth Damas et al, 2018). La llegada del diagnóstico supone una liberación para ellos (Cooper & Gilbert, 2017;Rosselló Aubach, 2017), sin embargo, no siempre se relaciona con mejoras en la atención y en la comunicación (Armentor, 2017;Triviño Martínez et al, 2016), de modo que los pacientes continúan percibiendo injusticia, incomprensión y un trato despectivo por parte de algunos proveedores de salud que creen que exageran los síntomas y que son producto de su imaginación (Cooper & Gilbert, 2017;Ramirez Carmona et al, 2014).…”
Section: Discussionunclassified
“…Los pacientes con una enfermedad crónica de etiología desconocida como la FM necesitan saber más acerca de su enfermedad para comenzar a aplicar estrategias que les permitan controlar su situación (Armentor, 2017). En este sentido, la comunicación por parte de los proveedores de salud es fundamental para conseguir la confianza del paciente y facilitar la toma de decisiones compartida que permita a la persona afectada participar activamente en su enfermedad (Homma, Ishikawa, & Kiuchi, 2016).…”
Section: Introductionunclassified